2021
DOI: 10.1108/jkm-04-2021-0277
|View full text |Cite
|
Sign up to set email alerts
|

Process innovation in the digital age of business: the role of digital business intensity and knowledge management

Abstract: Purpose This paper aims to examine the dynamic relationship between digital business intensity (DBI) and process innovation through knowledge management. More specifically, the paper investigates the mechanism through which DBI and knowledge management jointly influence process innovation. Design/methodology/approach The study used a single informant approach of data collection and consistent with prior research, and a random sample of CIOs was selected and invited to participate in the survey resulting in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 78 publications
2
29
0
1
Order By: Relevance
“… Nwankpa et al (2021) argued that there was no relationship between KA and performance of organizations in their previous study. This research contradicts their findings.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“… Nwankpa et al (2021) argued that there was no relationship between KA and performance of organizations in their previous study. This research contradicts their findings.…”
Section: Discussionmentioning
confidence: 85%
“… Shahzad et al (2020) considered KM to be a powerful tool for achieving corporate SD; however, the effect of FI on KMP-CSP relationships has not been studied. Further, Nwankpa et al (2021) emphasize the need for more research on KMP, FI, and sustainable performance.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge management Areed et al (2021) found although all of KM processes play an important role in an innovative organization, the most important one for innovation is to be knowledge sharing. Nwankpa et al (2021) examined the dynamic relationship between digital business intensity (DBI) and processes innovation through KM. In particular, they examined the mechanism by which DBI and KM jointly influence process innovation.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The work of Nwankpa et al (2021) looks at two new concepts which affect process innovation in the digital age: digital business intensity (DBI) – a measure of the level of strategic organizational investments in emergent and innovative digital technologies; and knowledge management – a critical resource for value creation and competitive advantage, the practices of which are closely linked to learning and problem-solving capabilities which in turn deliver innovative values. Knowledge management is considered as a step towards process innovation as it enables idea and knowledge sharing in a creative forum. …”
Section: The New Process Innovationmentioning
confidence: 99%
“…What is key to consider is that process innovation and digitalization do not necessarily converge, meaning that one does not lead to the other. As Nwankpa et al (2021) highlight, digitalization can result in complex transformation and redesign that can actually misalign process innovation outcomes. In fact, the comprehensive reliance on digital technologies in the last decade or so means that what constitutes successful process innovation has actually changed – the scope, features, and boundary conditions of process innovation has altered.…”
mentioning
confidence: 99%